The Art of Selling: Examining the Visual Aesthetic, Storytelling, and Impulsive Buying Decisions - Widyastuti, Pristiana (Journal of Applied Business Administration, 2024)
This research examined the visual aesthetic, storytelling, and impulsive buying decisions of home dÃ©cor products on Instagram. This research uses quantitative analysis with statistical tests. Data analysis using the Structural Equation Modeling (SEM) approach is a statistical method used to test cause-and-effect relationships between variables in a model. The statistical tool used is SmartPLS; it provides various statistics to evaluate model fit. The sample size was conducted on 100 Indonesian Instagram user accounts who had at least once purchased a product after viewing Instagram content related to home decoration using the link linked to the Instagram account. The results of studies presented that visual aesthetics have a significant influence on impulse buying behavior. In contrast, storytelling does not have a similar impact. Attractive visual aesthetics can increase consumers' tendency to make impulse purchases. On the other hand, a second study suggests that while storytelling may be compelling in building emotional connections with consumers, its lack of ability to create sufficient positive impressions may not be enough to encourage impulse buying.